A holistic approach to menstrual hygiene: Analyzing the interconnected roles of knowledge, socio-cultural correlates, and attitudes in adolescent girls - Fauziah, Hidayatul Auliya; Yualita, Perla; Kamila, Ami (Alma Ata University Press, 2024)
Background: Adolescent girls are vulnerable to reproductive health problems such as genitalia infections, due to lack of personal hygiene during menstruation. Adolescent girls' attitudes towards personal hygiene during menstruation can be influenced by several factors, including the level of knowledge about menstruation and socio-cultural aspects that influence perceptions of personal hygiene during menstruation.Objectives: This study was conducted to analyze the relationship between knowledge and social culture with attitudes about personal hygiene during menstruation among adolescent girls.Methods: This study uses quantitative correlation with a cross sectional approach. Sampling using purposive sampling with a total of 112 adolescent girls. The research was conducted at MTS Al-Hidayah Satron, Tasikmalya Regency in April-July 2023. Data were collected using knowledge, socio-cultural, and attitude questionnaires about personal hygiene during menstruation. Data were analysed using univariate and bivariate with Spearman rank.Results: The results of research on adolescent girls mostly have poor knowledge as many as 51 people (45.5%), most of them were 62 people (55,4%) with unsupportive socio-culture, and most of them were 65 people (58%) with negative attitude. The statistical test results showed that there was a relationship between knowledge and attitude about personal hygiene during menstruation with a p-value of 0.001 and there was a relationship between social culture and attitude about personal hygiene during menstruation with a p-value of 0.000.Conclusions: Knowledge and social culture of adolescent girls are associated with attitudes about personal hygiene during menstruation. Further research is needed to change the attitude of adolescent girls about personal hygiene during menstruation by increasing the knowledge and socio-culture of adolescent girls so that they can perform personal hygiene during menstruation.